Amyloid β–associated cognitive decline in the absence of clinical disease progression and systemic illness. Issue 1 (9th June 2017) - Harrington, Karra D.; Lim, Yen Ying; Ames, David; Hassenstab, Jason; Laws, Simon M.; Martins, Ralph N.; Rainey‐Smith, Stephanie; Robertson, Joanne; Rowe, Christopher C.; Salvado, Olivier; Doré, Vincent; Villemagne, Victor L.; et al.
Abstract: Introduction: High levels of amyloid β (Aβ) are associated with cognitive decline in cognitively normal (CN) older adults. This study investigated the nature of cognitive decline in healthy individuals who did not progress to mild cognitive impairment or dementia. Method: Cognition was measured over 72 months and compared between low (Aβ−) and high (Aβ+) CN older adults ( n  = 335) who did not progress to mild cognitive impairment or dementia and who remained free of severe or uncontrolled systemic illness. Results: Compared to the Aβ− group, the Aβ+ group showed no cognitive impairment at baseline but showed substantial decline in verbal learning, episodic memory, and attention over 72 months. Discussion: Moderate cognitive decline, particularly for learning and memory, was associated with Aβ+ in CN older adults in the absence of clinical disease progression and uncontrolled or serious comorbid illness.